Platelet immunology in fungal infections - Speth, Cornelia; Rambach, Günter; Lass-Flörl, Cornelia (Thrombosis and Haemostasis, 2014)
Up to date, perception of platelets has changed from key players in coagulation to multitaskers within the immune network, connecting its most diverse elements and crucially shaping their interplay with invading pathogens such as fungi. In addition, antimicrobial effector molecules and mechanisms in platelets enable a direct inhibitory effect on fungi, thus completing their immune capacity. To precisely assess the impact of platelets on the course of invasive fungal infections is complicated by some critical parameters. First, there is a fragile balance between protective antimicrobial effects and detrimental reactions that aggravate the fungal pathogenesis. Second, some platelet effects are exerted indirectly by other immune mediators and are thus difficult to quantify. Third, drugs such as antimycotics, antibiotics, or cytostatics, are commonly administered to the patients and might modulate the interplay between platelets and fungi. Our article highlights selected aspects of the complex interactions between platelets and fungi and the relevance of these processes for the pathogenesis of fungal infections.
Keywords: Platelets; fungi; invasive infection; innate immunity